Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Keaktifan Belajar Geografi Kelas X SMA Negeri 2 Solok - Erik Ekstrada; Momon Dt. Tanamir; Rozana Eka Putri (Departement of Mathematics Education, 2023)
The background of this research is the lack of active learning in class XE in geography subject at SMA Negeri 2 Solok. The purpose of this study was to find out and analyze the increase in the activeness of learning geography of students using the problem based learning (PBL) model for class X SMA Negeri 2 Solok. This type of research is quasi-experimental using a quantitative approach. The population in this study was class XE with a total of 391 people, with a random sampling technique in which the selected class was X E5 with a total of 36 people as the experimental class and X E11 with a total of 36 people as the control class. The research instrument uses a questionnaire and for data analysis uses a different test (t test). The results showed that the application of the problem-based learning model could increase the activeness of learning geography with a sig value of 0.004 <0.05. Furthermore, there is a difference in post-test scores with a sig of 0.000 <0.005.